Increased freedom of head movement mitigates stress and bacterial load in the airways of horses during transport - Takahashi, Yuji; Niwa, Hidekazu; Ebisuda, Yusaku; Mukai, Kazutaka; Yoshida, Toshinobu; Raidal, Sharanne; Padalino, Barbara; Ohmura, Hajime (Frontiers in Veterinary Science, 2024)
IntroductionProtection of horse welfare during transport is crucial. The aim of this study was to determine the effect of head and neck restraint on behavior and airway bacteria.MethodsIn a randomized crossover study, six healthy Thoroughbreds were transported by road for 22 h in an individual bay with tight head restraint (50 cm short-rope) or loose head restraint (95 cm long-rope). Behavioral parameters relating to head position, eating, and stress were monitored during transportation. Tracheal wash samples were obtained 6 days before and immediately after transport for bacterial culture and metagenomic analysis.Results and discussionCompared to before transport, bacterial load (CFU/mL) after transport was significantly increased in the short-rope group (p = 0.04), whereas no changes were observed in the long-rope group. Transport significantly reduced Simpson index at phylum, class, order, and family levels in both groups (p < 0.001) of tracheal microbiota. In both groups, this reduction was associated with increases in the dominant members of relative abundance at phylum (Firmicutes: +24% in long-rope and +14% in short-rope), class (Bacilli: +20% in long-rope and +22% in short-rope) and family (Streptococcaceae: +22% in long-rope and +23% in short-rope) levels. Licking behavior during transportation with short-rope restraint was more frequent than in horses with long-rope restraint. These results suggest loose head restraint during transportation is likely to ameliorate stress and mitigate the associated increased bacterial load in the lower airways associated with transport. Further, head position during transportation is likely a more important determinant of airway hygiene and distress than duration of travel.